PENGARUH KINERJA PEGAWAI REKAM MEDIS TERHADAP PENATALAKSANAAN PEMUSNAHAN REKAM MEDIS IN-AKTIF DI RSUD HAJI MAKASSAR TAHUN 2023 - Tariza Nurul Asfany R; Dian Ekawati; Zulkifli Zulkifli; Ryryn Suryaman Prana Putra (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Management of the destruction of inactive medical records is a process of reducing the number of medical records that are on active shelves by selecting inactive medical records and then moving them to the inactive medical record storage room, assessing and destroying those that have no use value in accordance with applicable policies. The purpose of this study was to examine the effect of medical record employee performance on the management of inactive medical record destruction.The type of research used is quantitative research with a cross section study design. This research was conducted with a sample of 30 respondents. Research data were taken through questionnaires and direct observation and data analysis techniques using univariate analysis and bivariate analysis.The results of this study indicate that the variable quality of work on the management of inactive medical record destruction with a sig value (1.000) > 0.05, the quantity of work on the management of inactive medical record destruction with a sig value (1.000) > 0.05, accuracy time to the management of the destruction of inactive medical records with a sig value (1.000) > 0.05, the effectiveness of the management of the destruction of inactive medical records with a sig value (1.000) > 0.05, independence of the management of the destruction of inactive medical records with sig value (1.000) > 0.05. The conclusion in this study is that there is no effect on the performance of medical record employees on the management of destroying inactive medical records at Haji Makassar General Hospital.